Time Budget Pressure as Moderating Variable on the Effect of Professionalism, Experience and Audit Fee on Audit Quality - I K A Wiguna; I B A Yasa; A A P Suardani (Journal of Applied Sciences in Accounting, Finance, and Tax, 2019)
Audit quality is the probability of an auditor where the auditor can find violations in his client's accounting system and report it in the audit report. Audit quality is influenced by various factors including professionalism, audit experience, audit fees and time budget pressures. This research aims to analyze the influence of professionalism, audit experience, and audit fees on audit quality, whether time budget pressures moderate the influence of professionalism, audit experience, and audit fees on audit quality. The population in this research are auditors who work at the Public Accounting Firm in Bali that were registered in the IAPI 2019 directory. The samples of this research are 70 auditors. This research use saturated sampling method. The analysis technique used in this research is modeling techniques with partial least square (PLS) through SmartPLS 3.0 application. The results of this research indicate that professionalism has a positive and significant effect on audit quality. Audit experience has a positive effect but not significant on audit quality. Audit fee have a positive and significant effect on audit quality. Time budget pressure does not moderate the influence of professionalism, audit experience and audit fees on audit quality.